Ambiente y TLC: el pacto de gobernabilidad - Rosell, Mónica (2007)
This paper aims at providing, from a sustainable development perspective, an idea about the direction our country will take once the US-Peru FTA is enforced, regarding particularly the environmental, trade and investment areas. The signing of the FTA has led Peru to leave behind a view of the environment vision as a moral and ethical (some times marginal) component of economic relations, to turn it into a regulatory and mandatory consideration overlapping trade and investment to such an extent that failure to comply may lead to sanctions as severe as those pertaining to other matters related to for instance access to or permanence in a given market. Even so, it is worthwhile mentioning that the FTA is only an initial component of a more complex and broad multilateral scenario that recognizes in the environment an essential element of international economic relations.